Integration Of Customary Legal Values And Modern Mediation In The Framework Of Land Dispute Resolution - Lubis, Ikhsan; Lubis, Duma Indah Sari; Lubis, Andi Hakim (jurnal.unprimdn.ac.id, 2025)
This study delves into the integration of customary law values with modern mediation in resolving land disputes in Indonesia, often marked by tensions between individual and communal interests as well as between customary law and national law. Employing a normative legal research methodology, this investigation explores relevant regulations, including the Basic Agrarian Law (UUPA) and the Law on Arbitration and Alternative Dispute Resolution, to understand how to harmonize the principles of customary law and mediation without undermining the supremacy of law at the national level. The research identifies two core issues: how distributive and procedural justice can be realized through this integration. Findings indicate that formal recognition of customary mediation outcomes and a comprehensive regulatory framework are crucial for establishing a fair and effective dispute resolution mechanism. This study advocates for the development of regulations that celebrate legal diversity, positioning land dispute resolution as a process that interweaves human values with local wisdom while simultaneously reinforcing the legitimacy of customary law within the national legal framework.